Urgensi Pengaturan Batas Usia Minimum Pengguna Media Sosial dalam Perlindungan Data Pribadi Anak - Rahma, Nita; Subagya, Rio; Suratmaja, Kenan (Legal Note, 2026)
The protection of children's personal data in digital spaces has become an urgent issue as social media penetration among minors continues to rise. This study examines the urgency of regulating a minimum age (age of consent) for social media users within Indonesia's personal data protection framework, referencing global regulatory developments from 2022 to 2026. A normative-juridical method with a comparative approach was employed, analyzing Indonesia's primary legal instruments—including Law No. 27 of 2022 on Personal Data Protection, Law No. 1 of 2024 (second amendment to the ITE Law), and Ministerial Regulation No. 9 of 2026—while benchmarking against regulations in the United States, European Union, United Kingdom, and Australia. The findings reveal that Indonesia has undergone a normative transformation from a regulatory vacuum to the explicit establishment of a 16-year age threshold through Ministerial Regulation No. 9 of 2026. However, critical gaps persist in privacy-preserving age verification mechanisms, cross-sectoral regulatory harmonization, and the absence of an independent Personal Data Protection Authority. Comparative findings indicate that a hybrid approach combining Safety by Design with age-based restrictions proves more effective than standalone prohibitions. This study recommends the development of derivative regulations under the Personal Data Protection Law specifically governing age assurance technical standards, as well as accelerated establishment of an independent supervisory body as mandated by Article 58 of the law.